1224. The incidence of severe C. striatum hospital-acquired pneumonia sharply increased and was associated with a high mortality rate. (15th December 2022) - Lee, Yun Woo; Huh, Jin Won; Hong, Sang-Bum; Jung, Jiwon; Jae Kim, Min; Pil Chong, Yong; Kim, Sung-Han; Sung, Heungsup; Do, Kyung-Hyun; Lee, Sang-Oh; Lim, Chae-Man; Soo Kim, Yang; et al.
Abstract: Background: The clinical information on patients with severe C. striatum pneumonia who require intensive care unit admission is currently limited. Methods: We investigated the incidence and characteristics of severe Corynebacterium striatum pneumonia during a 6-year period at Asan Medical Center in comparison with severe pneumonia associated with MRSA. Results: Between 2014 and 2019, there were 27 adult cases of severe C. striatum pneumonia. The majority of the cases (70.4%) were hospital-acquired pneumonia (HAP), and about half of the patients (51.9%) were immunocompromised. The incidence of C. striatum HAP significantly increased from 1.0% (2/200) in 2014-2015 to 5.4% (10/185) in 2018-2019 ( P < 0.001), while the incidence of severe methicillin-resistant Staphylococcus aureus (MRSA) HAP significantly decreased from 12.0% to 2.7% during the same period. Of the 75 HAP cases whose bacterial pathogens were identified in 2018–2019, C. striatum was responsible for 13.3% of the cases. The 90-day mortality rates were similarly high in the C. striatum and MRSA groups (59.3% vs. 50.5%, P = 0.42). Conclusion: In conclusion, C. striatum was a major pathogen of recent severe HAP and was associated with a substantially high mortality rate. Disclosures: All Authors : No reported disclosures.